The role of entrepreneurial marketing & innovation capability in the performance of SMEs during covid-19 pandemic: Evidence of MSMEs in West Java - Diana Sari; Belinda Aretha Kusuma; John Sihotang; Tri Febrianti (Cogent Business & Management)
The Corona Virus, or COVID-19, has become one of the world’s issues, not only affecting health but also the Indonesian economy. One of the sectors that has been impacted was micro, small, and medium enterprises (MSMEs), whose performance has decreased. Entrepreneurial marketing and innovation capability have proven to increase the performance of MSMEs. However, it was still questioned whether entrepreneurial marketing and innovation capability would increase performance during COVID-19 pandemic. We collected data through an online survey to 290 MSMEs in West Java. Statistical analysis using SmartPLS reveal that entrepreneurial marketing (opportunity-driven, proactiveness, customer intensity, risk taking, resource leveraging, and value creation) and innovation capability (product innovation, serve innovation, process innovation, and business model innovation) have a significant effect on the performance of MSMEs (profitability, productivity, domestic market share, profit margin, competitiveness of the MSMEs, ability to maintain profit margin, and rate owners satisfaction with innovation level). Innovation capability has a greater influence, with a value of 0.465, compared to entrepreneurial marketing, with a value of 0.156, on the performance of MSMEs. Serve Innovation and Process Innovation have a significant impact on the dimensions of innovation capability that contribute to MSMEs’ performance. Several practical and theoretical implications for entrepreneurs designing marketing strategies are discussed based on the findings.